2019
DOI: 10.6007/ijarped/v8-i4/6564
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Approaches in Teaching Writing Skill in ESL Classrooms

Abstract: This paper presents an analysis of a systematic review based on the past studies published on writing approaches employed in ESL classrooms. The studies reviewed are from the year 2000 to 2019 with the total number of eighteen studies. The key aims of this systematic review is to show an empirical information formulation discovered through multiple methods in past scholarly research on writing in ESL classrooms. In this systematic study, there are two study questions to be addressed: i) What teaching methods s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…Various approaches blended with strategies are essential in teaching of writing (Selvaraj & Aziz, 2019). According to Lavelle and Bushrow (2017), writing approach is described through the connection among the views the writers have on writing and the patterns of writing approaches that they use.…”
Section: Approaches To Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches blended with strategies are essential in teaching of writing (Selvaraj & Aziz, 2019). According to Lavelle and Bushrow (2017), writing approach is described through the connection among the views the writers have on writing and the patterns of writing approaches that they use.…”
Section: Approaches To Writingmentioning
confidence: 99%
“…According to Table 3, 18 studies were selected for the comprehensive review. This review done by Selvaraj and Aziz (2019), was chosen to be included in this systematic review on challenges in ESL writing classrooms and solutions to overcome them because this review shed some light on suitable approaches, how writing instruction should be planned and some recommendation for improvement. This systematic review suggested that the most suitable approach in teaching writing skills at secondary and tertiary level is to employ process based approach.…”
Section: A Systematic Review On Approaches In Teaching Writing Skillsmentioning
confidence: 99%
“…While using this model, the students are allowed to take control over their own writing and given opportunities to think like writers and make the "writers' decisions and choices" (Flower & Hayes, 1981, p. 377). Therefore, linguistic accuracy is no longer prioritized and exclusive attention is given to the mental processes instead (Selvaraj & Aziz, 2019).…”
Section: Theoretical Framework Of the Studymentioning
confidence: 99%
“…Sustainability 2021, 13, 9768 2 of 18 English for Specific Purposes (ESP) is, undeniably, more challenging because it deals with the terms and jargon of the English language for a particular context [8]. For instance, learning medical words in English requires specific vocabulary, which might not be part of common ESL.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing trends of research in ESP, systematic reviews are more towards the ESL [12][13][14], EFL [15][16][17], and ELT fields [18], thereby leaving a gap. Nevertheless, it is undeniably vital to look into the research trends in ESP, specifically in mobile learning, because ESP is specific.…”
Section: Introductionmentioning
confidence: 99%